1995
DOI: 10.1002/kin.550270608
|View full text |Cite
|
Sign up to set email alerts
|

Formation of HCOH + H2 through the reaction CH3 + OH. Experimental evidence for a hitherto undetected product channel

Abstract: In an extension of our earlier studies at lower temperatures [4,51 the title reaction was measured directly in a flow reactor at temperatures of 600 and 700 K. The pressure of 0.65 mb was chosen that low in order to reduce the contribution of the stabilization channel. OH was used in an excess over CH3. Both reactants along with the reaction products were monitored by mass spectrometry. CH3 profiles served as the major observable quantity for the extraction of rate data. This had to be done by using computer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
2
24
1
Order By: Relevance
“…Physically, they are responsible for the step with highest energy barrier, breaking and forming the bond between carbon and oxygen. Unfortunately, these reactions rates are not well studied and the measured rates reported in the literature are inconsistent (Baulch et al 1994;Humpfer et al 1994;Hidaka et al 1989). (See the discussion in Visscher & Moses 2011; In our network, we adopt the rate coefficients for reaction (13) from Jasper et al (2007) by considering its more recent publication date and more thorough treatment.…”
Section: Chemical Rate Coefficientsmentioning
confidence: 99%
“…Physically, they are responsible for the step with highest energy barrier, breaking and forming the bond between carbon and oxygen. Unfortunately, these reactions rates are not well studied and the measured rates reported in the literature are inconsistent (Baulch et al 1994;Humpfer et al 1994;Hidaka et al 1989). (See the discussion in Visscher & Moses 2011; In our network, we adopt the rate coefficients for reaction (13) from Jasper et al (2007) by considering its more recent publication date and more thorough treatment.…”
Section: Chemical Rate Coefficientsmentioning
confidence: 99%
“…55 Further reaction channels have been investigated through bimolecular reaction of electronically excited O( 1 D 2 ) with CH 4 56 -58 or through the recombination reaction of CH 3 with OH. 59 Hack and Thiesemann determined CH 2 O, 1 CH 2 , OH and ground state O( 3 P) from the unimolecular dissociation of chemically activated CH 3 OH by LIF. 56 At an excitation energy of 559 kJ mol Ϫ1 with respect to the vibrational ground state of CH 3 OH, they found that the unimolecular decay process is dominated by the OH-channel ͑90%͒ whereas the other decay channels are of minor importance: 6% for CH 2 O, 2% for 1 CH 2 and for O( 3 P).…”
Section: Unimolecular Dissociation Channels For Ch 3 Oh and Calculmentioning
confidence: 99%
“…56 At an excitation energy of 559 kJ mol Ϫ1 with respect to the vibrational ground state of CH 3 OH, they found that the unimolecular decay process is dominated by the OH-channel ͑90%͒ whereas the other decay channels are of minor importance: 6% for CH 2 O, 2% for 1 CH 2 and for O( 3 P). Humpfer et al investigated the bimolecular reaction of CH 3 with OH in a flow reactor at 700 K and a total pressure of 65 Pa. 59 For the reaction channels leading to HCOH, 1 60 although their analysis has been subject to questions. 61,62 The calculated transition state structures 53 and available thermochemical data 41,54 have been used to calculate k(E) for reaction channels ͑1͒-͑6͒ in Table I.…”
Section: Unimolecular Dissociation Channels For Ch 3 Oh and Calculmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the work of the Oser group (Oser et al 1992, Humpfer et al 1995. They describe difficult and complicated experiments, and the analysis of the data is subject to many uncertainties.…”
Section: Oh + Chmentioning
confidence: 99%